A potential role for two brainstem nuclei in craniovascular nociception and the triggering of migraine headache. (February 2021) - Zagami, Alessandro S; Shaikh, Sumaiya; Mahns, David; Lambert, Geoffrey A
Aim: To use an animal model of migraine to test whether migraine headache might arise from a brainstem-trigeminal nucleus pathway. Methods: We measured evoked and spontaneous activity of second-order trigeminovascular neurons in rats to test whether the activity of these neurons increased following the induction of cortical spreading depression or the imposition of light flash – two potential migraine triggers, or headache provokers. We then tested whether drugs that could activate, or inactivate, neurons of the nucleus raphe magnus or the periaqueductal gray matter, would affect any such increases selectively for the dura mater. Results: Injection of sodium glutamate (a neuronal excitant) into these two nuclei selectively inhibited the responses of trigeminovascular second-order neurons to dura mater, but not to facial skin, stimulation. Injection of lignocaine (a local anaesthetic) into these nuclei selectively potentiated the responses of these neurons to dura, but not to facial skin, stimulation. Furthermore, injections into either nucleus of glutamate inhibited the increase in the ongoing discharge rate of these neurons produced by cortical spreading depression and light flash. Conclusions: These results provide indirect evidence that trigeminovascular nociception may be tightly controlled by these two nuclei, whereas cutaneous trigeminal sensation may be less so. These nuclei may be relays of one possible brainstem-trigeminal pathway that could mediate migraine headache. Modification of neuronal activity in these two nuclei produced by migraine (headache) triggers may lie behind the pain of a migraine attack, at least in some cases.